Food choices among Portuguese teenagers: a case study - Guimarães, Maria de Fátima (2023)
The Mediterranean Dietary Pattern (MDP) is currently accepted as being protective against some of the most worrisome chronic non-communicable diseases in today's society. It is important to instil this nutritional pattern in young people as it is at this point in life that healthy eating habits are created and later maintained. Assessing the adherence of students to the Mediterranean Dietary Pattern (MDP). A case study was carried out with 463 students aged between 14 and 20 years old. Parents of the youngsters were also surveyed to find out about the accuracy of the youth's answers and to determine the type of food preparation practiced in the family. Those who participated in this study had an informed consent, previously signed by their parents and voluntarily expressed their willingness to participate, although they could drop out at any time if they so wished. The results showed a good adherence to the Mediterranean Dietary Pattern (MDP) by the respondents (46.47%) and their knowledge about the concept of the Mediterranean Diet can be classified as “good” (39.7%) and “reasonable” (36.6%). The main conclusions of the study are that the students participating in the study have a good knowledge about the Mediterranean Food Pattern and show a high level of adherence to it.